Dzikir Sebagai Intervensi Mind Healing Technique Terhadap Konsentrasi Belajar Di Kalangan Anak Asuh Panti Asuhan Al-Falah Yasmuba Bandar Lampung - Berta, Afifah; Anshori, Afif; Mu’asyara, Nesia; Haris, Muhammad (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
This research aims to evaluate the effectiveness of dzikr (Islamic devotional acts) using the Mind Healing Technique (MHT) approach in improving the learning concentration of female foster children at Al-Falah Yasmuba Orphanage. The research method used a quasi-experimental design with a pretest-posttest single group approach. Participants consisted of 34 female foster children aged 12-19 years who were given MHT dhikr intervention for 4 weeks, 3 times a week, with a duration of 20-30 minutes per session. Data was collected through observation, questionnaires, and interviews, then analyzed using parametric statistical tests (paired t-test) with SPSS 30. The results showed a significant increase in the average learning concentration score from 104.65 (pretest) to 116.15 (posttest), with an increase of 11.50 points (p < 0.001). The large effect of the intervention (Cohen's d = 0.943) indicates that MHT dhikr is effective in improving learning concentration. Therefore, it can be concluded that dhikr with the MHT approach can be an effective intervention to improve learning concentration, especially in orphanage environments. It is recommended that this technique be integrated into learning programs and further research be conducted with more complex designs to test the generalization of findings.